Ionic liquid and deep eutectic solvent-enabled food freshness sensing: From molecular interactions to integrated intelligent monitoring systems - Xinhui Zhou; Yuan Huang; Yuping Liu; Zhangyan Sun; Yuxiao Hu; Mingfeng Xu; Xueqin Yang; Rongrong Yu (Trends in Food Science & Technology, 2026)

De novo transcriptome profiling reveals the bioeffect of the clam (Cyclina sinensis) to graded extremely low-frequency electromagnetic fields (ELF-EMF, 50 Hz) exposure - Mingming Zhang; Yuqing Fan; Mingfeng Zhu; Shouhai Liu; Hu Zhang; Chaojun Gu; Zhenyu Wang; Boping Yang; Guo Qiao (Environmental Pollution, 2026)

Adaptive graph learning with dynamic neural ODE for feeding intensity analysis of pearl gentian grouper in a recirculating aquaculture system - Hongpo Wang; Zeshuang Ma; Hong Zhou; Yunchen Tian; Haohui Liu; Zhanshuo Sun; Lei Jia; Jincheng Hu; Mingfeng Hu (Aquacultural Engineering, 2026)

Evaluation of novel probiotic Bacillus candidates from the midgut of gibel carp (Carassius auratus gibelio): effects on fish growth, immunity, and resistance to CyHV-2 infection - Mingming Zhang; Ni Ma; Yaqin Yang; Mingfeng Zhu; Hu Zhang; Zhigang Zhao; Jialin Zhang; Mingzhu Pan; Zhitao Qi; Guo Qiao (Aquaculture International, 2026)

Comparative analysis of fully-coupled towing simulation for a 15MW floating wind turbine using FAST2AQWA method - Mingsheng Chen; Suqian Liu; Xingyu Jiang; Mingfeng Hu; Zhuo Li; Jiale Jiang; Junyu Li (Ocean Engineering, 2026)

Morphology-Controlled Alumina-Supported MoS2 catalysts for enhancing hydrogenation and hydrodenitrogenation via metal clusters - Chenxi Li; Aiguo Zheng; Hong Nie; Wei Han; Mingfeng Li; Anpeng Hu; Le Zhang; Huifeng Li (Fuel, 2025)

Combined techniques for antigen-specific nanobody discovery in the white-spotted bamboo shark (Chiloscyllium plagiosum) - Bo Zhong; Junjie Yang; Kaixi Zheng; Wenjie Tang; Lei Jia; Mingfeng Gu; Jinming Hu; Xiaofeng Jiang; Jianqing Chen; Zhengbing Lyu; Guodong Chen (Fish & Shellfish Immunology, 2025)

Isolation and structural elucidation of two novel lignans from the flowers of Gardenia jasminoides with potent α-glucosidase inhibitory activity - Qingsen Shao; Huiyu Li; Mingfeng Li; Wei Yi; Qiugui Zhou; Lijuan Zheng; Meng Wang; Hong-mei Hu; Chao Wen; Yun Tang; Wei Li (Phytochemistry Letters, 2025)

Identification of volatile indicators for quality deterioration of Yu-Shiang Shredded pork after reheating based on HS-GC-IMS and intelligent sensory evaluation - Chunyuan Ping; Honglian Hu; Jicai Bi; Xiang Li; Yuwen Yi; Mingfeng Qiao (International Journal of Gastronomy and Food Science, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

Multi-classification prediction of PM2.5 concentration based on improved adaptive boosting rotation forest - Tan Deng; Yingzi Jia; Ni Liu; Xiaoyong Tang; Mingfeng Huang; Wenzheng Liu; Xinjiang Hu; Yanling Gu (Journal of Environmental Chemical Engineering, 2024)

Current Status and Future Trends in Installation, Operation and Maintenance of Offshore Floating Wind Turbines - Mingfeng Hu; Jinkun Shi; Sheng Yang; Mingsheng Chen; Yichang Tang; Suqian Liu (Journal of Marine Science and Engineering, 2024)
The installation and operation phases are critical stages in the lifecycle of offshore wind turbines, with costs associated with the installation and maintenance of floating wind turbines accounting for approximately 50% of the total investment. This paper presents the latest advancements in the technologies for the installation and maintenance of floating wind turbines. First, it discusses the installation techniques and relevant research related to the foundations and components of floating wind turbines. Next, it explores various operational strategies for offshore wind turbines and studies on major component replacements. The interrelationship of research in the installation and maintenance fields for floating wind turbines is examined. Furthermore, this paper investigates various tools and equipment used for the installation and maintenance of offshore wind turbines. It also addresses the relevant regulations and standards governing offshore operations for floating wind turbines. Finally, this paper provides a forward-looking perspective on the installation and maintenance of floating wind turbines.

Dynamic Analysis of Crane Vessel and Floating Wind Turbine during Temporary Berthing for Offshore On-Site Maintenance Operations - Jinkun Shi; Mingfeng Hu; Yifan Zhang; Xiaodong Chen; Sheng Yang; Thiago S. Hallak; Mingsheng Chen (Journal of Marine Science and Engineering, 2024)
With the increased scale and deployment of floating wind turbines in deep sea environments, jack-up installation vessels are unable to conduct maintenance operations due to limitations in water depth. This has led to the recognition of the advantages of floating cranes in offshore maintenance activities. However, the dynamic coupling between the crane and the floating wind turbine under wave and wind action can result in complex responses, which also relate to complex mooring configurations. The ability to maintain stability during maintenance operations has become a primary concern. In order to address this issue, a method of connecting a floating crane with a floating wind turbine is proposed, simulating the berthing of a floating offshore wind turbine (FOWT) to a crane. Thus, a systematic comparison was conducted with frequency- and time-domain simulation using ANSYS-AQWA software. The simulation results demonstrated the feasibility and dynamic efficiency of this novel berthing approach. Connecting the crane vessel to a floating wind turbine significantly reduced the crane tip movement. Simulations showed that the crane tip movement in the X-, Y-, and Z-directions was reduced by over 30%, which implies that it may be feasible to conduct offshore on-site maintenance operations for the FOWT by using floating crane vessels if the two bodies were properly constrained.

Design of active phase structure with high activity and stability in residue hydrotreating reactions - Yanzi Jia; Anpeng Hu; Dawei Hu; Mingfeng Li; Huifeng Li; Qinghe Yang; Zhiwei Liu; Zhicai Shao; Shuangqin Zeng; Xinqiang Zhao; Yifan Wang (Fuel, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

Evaluation of three prevalent global riverine nutrient transport models - Xinyi Jiao; Jia Zhou; Minpeng Hu; Mingfeng Wang; Hao Wu; Kaibin Wu; Dingjiang Chen (Environmental Science and Pollution Research, 2023)

Insight into the effect of microplastics on the adsorption and degradation behavior of thiamethoxam in agricultural soils - Mingfeng Hu; Lulu Huang; Ya Wang; Huihua Tan; Xiangyang Yu (Chemosphere, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Cement replacement with brick powder and concrete powder in sludge solidification - Junfeng Ni; Xiuqing Hu; Feiyu Liu; Chengan Zhu; Li Mingfeng; Jinqiang Jin; Changfei Gou (Marine Georesources & Geotechnology, 2022)

Behaviour of electroosmotic consolidation by electrode configuration and fracture grouting - Yunguo Du; Chao Zhang; Changfei Gou; Wenwen Wu; Xiaobing Li; Xiuqing Hu; Wang Chaoliang; Li Mingfeng (Marine Georesources & Geotechnology, 2022)

Effect of initial deviatoric stress on anisotropy of marine clay during principal stress rotation - Heng Zhuang; Xiuqing Hu; Lin Guo; Li Mingfeng; Wang Chaoliang; Hongke Du; Jingqiang Jin (Marine Georesources & Geotechnology, 2022)

The optimal combination form of vacuum pre-loading combined with electro-osmosis and with dynamic compaction method on the improvement of dredged slurry - Xiuqing Hu; Ziyang Gao; Feiyu Liu; Yu Tao; Donghai Xu; Yunguo Du; Changfei Gou; Mingfeng Li (Marine Georesources & Geotechnology, 2021)

Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading - Dikang Zhang; Hongtao Fu; Jun Wang; Dongqi Zhu; Xiuqing Hu; Yunguo Du; Changfei Gou; Chaoliang Wang; Mingfeng Li; Hai Wu (Marine Georesources & Geotechnology, 2021)

Pyruvate decarboxylase and alcohol dehydrogenase overexpression in Escherichia coli resulted in high ethanol production and rewired metabolic enzyme networks - Mingfeng Yang; Xuefeng Li; Chunya Bu; Hui Wang; Guanglu Shi; Xiushan Yang; Yong Hu; Xiaoqin Wang (World Journal of Microbiology and Biotechnology, 2014)